Treatment of nocturnal leg cramps by primary care patients over the age of 60. (24th July 2017) - Lorenzo, Mathieu; Schaeffer, Mickaël; Haller, Dagmar M; Maisonneuve, Hubert
Abstract: Background: Approximately one out of two individuals over the age of 60 suffers from nocturnal leg cramps. These often have an important impact on the person's quality of life. Different drug and non-drug treatments are proposed to treat these cramps, but none to date have been shown to be both safe and effective. The objective of this study was to describe the drug and non-drug treatments used by primary care patients suffering from cramps. Methods: We used data collected as part of two cross-sectional surveys of patients aged 60 years and older attending general practices in the French region of Alsace. We asked the participants suffering from cramps if they were currently using a treatment for their cramps. We distinguished potentially harmful from unharmful treatments. Results: Overall, 632 patients suffering from cramps were included in our study. Only 133 patients (19.5%) were taking a treatment for cramps. 82 patients used one or several of 17 different drug treatments. 58 patients used one or several of 13 different types of non-drug treatments. Potentially harmful treatments, mostly Quinine made up 16, 7% ( n = 25) of all treatments used for cramps. Conclusions: This study sheds light on the great diversity of therapeutic practices for cramps in outpatient care. Many of the treatments reported by patients have not previously been described in the medical literature. We recommend GPs to ask their patients about the treatments they take for cramps in order to make sure that they are safe.